The South Caucasus and regional actors through the prism of the typology of cultural dimensions of G. Hofstede: comparative analysis - A. A. Tonian (Современная наука и инновации, 2023)
This article attempts a comparative analysis of the countries of the South Caucasus using the typology of cultural dimensions of G. Hofstede, and also considers, through this typology, countries that claim leadership in the region, namely Iran, Russia and Turkey. Since the author of the article understands leadership not only as military-political and economic superiority, but also cultural (which is especially important in the context of considering the policy of soft power), it seems necessary to include the above-mentioned countries in the object of analysis. This will allow us to understand the specifics of interethnic relations through the measurement of cultures.